Upaya Guru Dalam Mengajarkan Bahasa Indonesia Bagi Anak-Anak Paud Di Desa Raba Ege - Ninsi Risna Boimau (Lembaga Pengembangan Kinerja Dosen, 2024)
Raba Ege Village is one of the villages located in the sub-district of West Wewa, Southwest Sumba Regency. This is where the community service activities are held. Based on the results of observations and surveys conducted, it turns out that children in Raba Ege village still lack understanding and knowledge in Indonesian. As a result of this problem, children in Raba Ege village are very embarrassed when they meet people from outside Sumba (migrants). As a form of responsibility and concern, this community service is present as an answer to these needs. The goal is that children in raba ege village can become individuals who are responsible for themselves and help children in raba ege village to be able to communicate using Indonesian. The implementation of this community service uses the method of translators, sign language, surveys, discussions, and is supported by literature studies. The results obtained from this effort are that children in Raba Ege village can communicate (speak) using good and correct Indonesian.